Laporan Kasus : Pasien Anak 12 tahun dengan Katarak Juvenil Okuli Dekstra - Ananda Fitriliani; Muhamad Maulana (CV. Jasa Sukses Abadi, 2025)
Juvenile cataract is one of the leading causes of visual impairment in children and adolescents, either due to congenital abnormalities or acquired factors. This condition may significantly reduce quality of life and carries a risk of amblyopia if not managed promptly. We report a 12-year-old boy presenting with blurred vision in the right eye for the past seven months, worsening within the last month. The patient complained of cloudy vision, difficulty seeing both near and far objects, and frequent glare. His mother noticed a whitish spot on the right eye. Ophthalmological examination revealed visual acuity of 1/300 in the right eye, leukocoria, whitish lens opacity, and a positive shadow test, while the left eye was within normal limits. The patient was diagnosed with juvenile cataract in the right eye and scheduled for cataract extraction with intraocular lens (IOL) implantation.